Case to Project Method in the Learning of Speaking - Tanti Kurnia Sari; Surya Masniari Hutagalung; Indah Aini; Siti Kudriyah (BIRCU, 2021)
The government policies on MBKM encourage the university to apply case-based learning and project-based learning. Thus, by inserting the case study in learning is the right thing to produce qualified learning. Based on the statement above, this research is aimed at developing the learning to speak by using case method. This research is carried out at the studies program of German Education, Faculty of Languages and Arts, Universitas Negeri Medan. This research was categorized as a Development Research which aimed to produce teaching materials for speaking skill by integrating the case method. The development step used is the Reeves development step, namely Design Based Research which consists of: (1) Problem Identification, (2) Draft Development, (3) Repeated Testing, and (4) Reflection to Generate Solutions. However, in this research, the focuses on this research are on problem identification and draft development. The data in this study are qualitative data which came from books and the Internet. The teaching materials developed were adapted to the themes for B1 contained in the Studio Express B1 book, which is a mandatory textbook for students at the level of B1. The integration of case method in learning to speak is done in four steps, they are: 1) Identifying problems and continuing with investigations, 2) Providing context, 3) Providing clear rubrics and 4) Setting the structure of presenting solutions through reflection. By integrating the case method in learning to speak, it is hoped that it can improve students' speaking competence as well as improve students' ability to find solutions to a problem.